2021
DOI: 10.1177/00469580211060797
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Psychiatric Disorders and Clinical Factors Associated With a Schizophrenia Diagnosis

Abstract: Background Schizophrenia (SCH) and bipolar disorder (BD) have both shared and unique genetic risk factors and clinical characteristics. The aim of the present study was to identify potential risk factors significantly associated with SCH, relative to a BD reference group. Methods Data were obtained from medical records of patients that entered a major Mexico City hospital during 2009–2010 presenting psychotic symptoms (n = 1132; 830 cases of SCH, 302 cases of BD; 714 men and 418 women). SCH and BD diagnoses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…In the present study, as in a previous analysis of the same patient population [ 33 ], there were notable differences between male and female patients with regard to several measures (for a review of gender differences in SCH see Ochoa et al 2012 [ 34 ]). Notably, men were twice as likely than women to report having dropped out of school at the secondary or high school levels.…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, as in a previous analysis of the same patient population [ 33 ], there were notable differences between male and female patients with regard to several measures (for a review of gender differences in SCH see Ochoa et al 2012 [ 34 ]). Notably, men were twice as likely than women to report having dropped out of school at the secondary or high school levels.…”
Section: Discussionsupporting
confidence: 75%
“…This finding was also obtained in another review study investigating the neuropsychiatric side effects of chloroquine (63). The results of the current literature review showed that most patients had no family or personal history of psychiatric disorders, although the risk of psychiatric events may be influenced by familial risk (64). It can be a practical warning notice for healthcare providers that expect psychiatric manifestations following chloroquine therapy in patients with no previous history.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, this gap in mortality rates is continuing to widen ( Tanskanen et al, 2018 ). Environmental factors, such as social isolation, childhood trauma, urban living, and ethnicity, are considered to be among the multifactorial causes of SCZ ( Diaz-Castro et al, 2021 ; Srivastava et al, 2021 ). SCZ may have its origins in utero , with obstetric potential risk factors including complications such as low birth weight, gestational diabetes, bleeding, asphyxia, and emergency caesarean section.…”
Section: Introductionmentioning
confidence: 99%